THE EFFECTS OF EXTENSIVE LISTENING ON EFL LEARNERS’ LISTENING COMPREHENSION - Yen, Tran Thi Ngoc; Thao, Tran Thi Phuong (VNU Journal of Foreign Studies, 2021)
The teaching of listening seems to be an under-researched topic (Field, 2008) although scientists have asserted that listening is an integral part of language development. This study examines the employment of extensive listening as a method to enhance EFL learners’ listening comprehension. The experiment in the study involved two intact classes with 42 learners attending an English program at a language center in Vietnam. An extensive listening program was set up for the treatment group to follow. The control group, in the meantime, was given listening exercises as homework. A pre-test and post-test was used to measure the participants’ improvement in listening comprehension. The results showed that the treatment group significantly outperformed their control group counterparts. This suggests that extensive listening facilitates EFL learners’ listening comprehension.